A Harmoni Mode Muslimah Milenial: Eksplorasi Tren Fashion dari Konservatif ke Modis dengan Lensa Agama di Indonesia - Putri Habibillah; Rubaidi; Hanun Asrohah (JURNAL PENELITIAN, 2024)
The purpose of this article is to analyze the fashion trends of millennial Muslim women from conservative to modern perspectives within the framework of religion in Indonesia. The backdrop of this research is the ongoing discourse between groups that argue that millennial Muslimah fashion should adhere to Islamic Sharia principles and those advocating for a more modern and stylish representation of Islamic identity to the general public. The research employs a Systematic Literature Review (SLR) indexed in Scopus using the Watase Uake tool, Publish or Perrish, publications from international journals such as Springer and Taylor and Francis, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique, narrowing down from 281 articles to 16 selected as research data. Millennial Muslimah fashion in Indonesia has undergone evolution from its introduction to innovation. Initially faced with hierarchy and prohibitions, it has now transformed into a stylish trend reflecting piety, innovation, and global influences. This transformation is influenced by the conflicting paradigms of right-wing and left-wing Islam, leading towards a moderate Islamic stance. A new identity for millennial Muslimah fashion has emerged through phenomena like hijabers, hijrah groups, and pop culture, creating a style that combines Islamic values with contemporary trends.